2013
DOI: 10.5296/ajfa.v5i1.3687
|View full text |Cite
|
Sign up to set email alerts
|

Global Financial Crisis and Role of Ownership Structure on Cost of Capital

Abstract: This paper explores the relationship between ownership structure and cost of capital. Prior studies have established links between ownership structure, firm performance and cost of capital but their results are mixed and inconclusive. As ownership structure is one of the important issues faced by corporates, especially in listed companies, the objective of this study is to explore the relationship between ownership structure and cost of capital in listed companies. In addition, the role ownership structure pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…This ownership is the percentage of shares owned by managers in the company. A previous study has shown that managerial ownership can mitigate information asymmetry and reduce the cost of equity capital (see [56]). The fifth measure is foreign ownership.…”
Section: Measurement Of Ownership Structurementioning
confidence: 99%
“…This ownership is the percentage of shares owned by managers in the company. A previous study has shown that managerial ownership can mitigate information asymmetry and reduce the cost of equity capital (see [56]). The fifth measure is foreign ownership.…”
Section: Measurement Of Ownership Structurementioning
confidence: 99%